The structural design and superplastic forming/diffusion bonding of Ti2AlNb based alloy for four-layer structure. (15th August 2016) - Du, Zhihao; Jiang, Shaosong; Zhang, Kaifeng; Lu, Zhen; Li, Baoyong; Zhang, Dalin
Abstract: The multilayer structure of Ti2 AlNb based alloy was fabricated based on the superplastic forming/diffusion bonding (SPF/DB) in this paper. The properties of superplasticity and diffusion bonding of Ti-22Al-27Nb alloy were investigated. The uni-axial tensile experiment showed that the tensile elongation reached up to 236% at the temperature of 970 °C with the strain rate of 3 × 10 − 4 s − 1 . Based on the superplasticity, the finite element analysis of structural design was carried out and the results showed that the honeycomb structure was flexible. And the diffusion bonding experiment was carried out at the temperature of 950 °C and 970 °C. Combining the microstructure of bonding interface with shear strength of different joints, the diffusion bonding parameter for present alloy was: 970 °C/10 MPa/2 h. The thickness distribution of the final structure was uniform and consistent with that of the FEA result, and the mechanical properties after SPF/DB reduced and the compressive strength of this structure behavior was about 7.7 MPa. Graphical abstract: Highlights: The Ti-22Al-27Nb alloy exhibited superplasticity with a elongation of 236% at 970°C / 3 × 10 -4 s -1 and could be bonded well at 970°C/10MPa/2h. The mechanical properties were compared between as-received sheet and post-SPF/DB face sheet at room temperature and elevated temperature. The superplastic forming/diffusion bonding process of honeycomb structure for Ti-22Al-27Nb alloy was feasible and it was an effective way to fabricated this structure.